Quality of Thai Traditional Medicine Graduate as standard of Thai Qualifications Framework for Higher Education from Kanchanabhishek Institute of Medical and Public Health Technology, Year 2015 - บุญเพียร, อำพล; จันทรพล, ปฐมา; สุริรักษ์, สุทธิศักดิ์; หมั่นพลศรี, เอกพล (Journal of Research and Development Buriram Rajabhat University, 2018)
This survey research aimed to evaluate and compare quality of Thai traditional medicine graduates according to Thai Qualifications Framework for Higher Education of Kanchanabhishek Institute of Medical and Public Health Technology in academic year 2015. The data were collected from the opinions of 40 graduates and their employers from May to July 2017. The tool used in this study was a questionnaire comprised 6 aspects of the quality of graduates according to Thai Qualifications Framework for Higher Education. The content validity of the questionnaire was tested by 3 experts. Percentage, mean ( ), standard deviation (SD) and Independent sample T-test were applied to analyze the data. The results based on the opinions of the employers showed that overall quality of academic year 2015 Thai traditional medicine graduate was at a high level ( =3.99, S.D. =0.16). When considered in each aspects, it was found that the quality in moral and ethics achieved the highest average ( = 4.21, S.D. = 0.57). In addition, the results based on graduates’ opinions suggested that overall quality of academic year 2015 Thai traditional medicine graduate was at a high level (=3.90, S.D. = 0.22) in which the quality in moral and ethics earned the highest average ( = 4.25, S.D. = 0.46). The comparison between the opinions of employers and graduates revealed that the quality of Thai traditional medicine graduates was not statistically different at the significant level of 0.05.